Heat transfer analysis on creeping flow Carreau fluid driven by peristaltic pumping in an inclined asymmetric channel. (1st June 2020) - Noreen, S.; Kausar, T.; Tripathi, D.; Ain, Qurat Ul; Lu, DC.
Highlights: A mathematical model carrying fluid in an inclined microvessel led by heat transfer. Realistic applications of this model are blood flow via capillary and microvessels. Heat transfer analysis is also considered under the viscous dissipation effect. The coupled and non-linear system is solved analytically. The results can be used in diagnosis/mixing of samples and hemodialysis respectively. Abstract: In this paper we have analyzed the heat transfer characteristics of Carreau fluids. Fluid is transported in an inclined asymmetric channel via peristalsis in the presence of an inclined magnetic field. Analysis is done in wave frame of reference. Complex governing equations for Carreau fluids are simplified by using the approximations of long wavelength and low Reynold number. Perturbation Technique is used to find out the approximate series solutions for stream function, pressure gradient, temperature and pressure rise. This magnetohydrodynamic pumping of non-Newtonian physiological liquid revealed interesting observations for design of peristaltic pump. It is found that the temperature characteristics are strongly enhanced and controlled by the angle of inclination of magnetic field. Furthermore, the velocity contour of fluids shows less drag as compared to viscous fluid and is effectively controlled by regular parameters, viz., Hartmann and Carreau fluid parameters. The study is pertinent to MHD blood pumps.